Isolation of Endophytic Bacteria from Sugarcane and Its Role as Biocontrol Agents and Plant Growth Inducer - astri afriani (Jurnal Penelitian Agrosamudra, 2017)
Studies on endophytic bacteria has been increasing recently due to its potency to promote plant growth and induce plant tolerance to pests and diseases. The research was undergone to isolate endophytic bacteria from sugarcane followed by evaluation of their biocontrol and plant growth activities. Isolation of endophytic bacteria was based-on surface-sterilized method using alcohol 70% and 0,1% HgClâ‚‚ on NA media. The result showed: 10 isolate endophytic bacteria had isolation were: B1, B2, B3, B4, B5, B6, B7, B8, B9, and B10. Three isolate had clear zone on petridish â‰¥ 20 mm in vitro testing is B9, B7, and B2. The results showed of endophytic bacteria filtrate test B2 produces alkaloid and terpenoid compounds, B7 contains saponin flavonoid, tannin and terpenoid compounds and B9 contains alkaloid, tannin and terpenoid compounds. This indicated that some of the endophytic bacteria have the potency as biocontrol agents and inducer of plant growth.